Management skills and change management of Public Technological Higher Education Institutes - Plasencia Castillo, Jaime Yvan (2021)
The purpose of this research was to determine the relationship between managerial competencies and change management of Institutes of Higher Technological Public Education, La Libertad Region, 2020. Methodology, basic type research, quantitative approach, non-experimental design, hypothetical-deductive method, a stratified probability sample of 112 participants. The survey technique with high reliability was used through Cronbach's Alpha of 0.988, for change management of 0.995. Results, it was determined that Kendall's Tau-b test = 0.561 and Spearman's Rho coefficient = 0.754 (high positive relationship), with a significance level of less than 1%. Conclusion, it was found that managerial competencies are directly and very significantly related to the management of change in Public Technological Higher Education Institutes, La Libertad Region, 2020, consequently, the research hypothesis is accepted. The development of managerial skills based on workshops is proposed; using specific and appropriate techniques to achieve the development of skills.